Dual Spherical Spline and Its Application in Tool Path Planing for 5-Axis Flank Milling - Zhou, Yayun; Schulze, Jörg; Schäffler, Stefan (Communications in Computer and Information Science, 2013)
Dual spherical spline is a newly proposed spline which is an alternative representation of ruled surfaces. This representation has advantages in the ruled surface manufacture due to its close relation to kinematics. In this paper, a new tool path planning approach is proposed based on the offset theory and the kinematic ruled surface approximation. The novelty of this approach is to denote the drive surface as a dual spherical spline, which provides a convenient conversion to the tool motion. Based on this representation, a novel design and manufacuture process is proposed to derive a flank millable surface. The designed surface is represented as a flank milling tool path with a cylindrical cutter in CNC machining. This approach delivers more accuracy compared with convectional tool position optimization methods. By integrating the manufacture requirements into the design phase, this approach also reduces the developing cycle time and the manufacturing cost. © Springer-Verlag Berlin Heidelberg 2013.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Blade design; Dual spherical spline; Flank milling; Manufacture; Ruled surface